Analysis of Expressive Speech Acts on the 2017 IPSE YouTube Channel about Panel Discussion of Language Education Course Papers Indonesia IPSE students 2017 - Sri Nani Herawati; Fahda Kurnia Palupy; Eka Budiarti; Faiza Munira; Asep Purwo Yudi Utomo (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Speech acts are illocutionary acts that function to express an assessment of the circumstances specified in the illocutionary, for example saying thank you, expressing condolences, and so on. The research objectives to be achieved in this study are: (1) to reveal the types of expressive speech acts contained in the YouTube channel IPSE (International Program on Science Education) 2017 regarding Panel Discussion of Language Education Course Papers, (2) to Identify forms of speech acts in learn Language Education Course Paper Panel. This research is a descriptive study that in the end tries to describe the speech spoken by the object, which is in accordance with the actual picture. In this study, the method used is the referential method. The listening method was used in this study because the data or object used is in the form of spoken language. there are 59 expressive speeches in 7 videos on the YouTube channel IPSE (International Program on Science Education) 2017 regarding the Panel Discussion of Language Education Course Papers. Among them are asking for 7 as many utterances, apologizing as much as 38 38, and criticizing as many as 14 utterances. This research is expected to provide benefits to readers or the public in the form of increasing understanding of expressive speech acts.